Tineoidea (Meessiidae, Tineidae) and Glyphipterigidae: Acrolepiinae from the Canary Islands, Spain (Insecta: Lepidoptera) - R. Gaedike; P. Falck (SHILAP, 2019)
Based on recent field work and examination of specimens of the families Meessiidae and Tineidae (Tineoidea) and the subfamily Acrolepiinae (Glyphipterigidae) we record the following three species as new to the Canary Islands: Xystrologa grenadella (Walsingham, 1897) (Meessiidae), Nemapogon granella (Linnaeus, 1758), and Tinea translucens Meyrick, 1917 (Tineidae). Haplotinea insectella (Fabricius, 1794) is deleted from the Canary Islands list. We also describe one hitherto undescribed species: Neurothaumasia betancuriacola Gaedike & Falck, sp. n.. For a further 31 species, hitherto known from the Canary Islands, we established first records for several islands. A checklist of the 50 taxa now known from the Canary Islands is presented, with indications of the sources of records.